Les tribulations parisiennes de l’officier écrivain : l’oeuvre autobiographique de Yasmina Khadra et son accueil en France - Pawlicki, Jędrzej (Wydawnictwo Naukowe UAM, 2012)
This article describes Yasmina Khadra’s autobiographical work composed of two books: "L’écrivain" and "L’imposture des mots" and its reception in France. The main purpose of this study was to establish the literary genre of these books, which implies determining whether Khandra’s work represents an autobiography or an autofiction with reference to P. Lejeune’s and V. Colonna’s theoretical studies. The dividing line between two genres in Khandra’s works refl ects his inner split between being either a solder or a writer. The presentation will also help to understand the controversy resulting from Khandra’s participation in Algerian civil war. Moreover the analysis is related to modern Algerian history.
Afflictions encountered in Paris by an army officer and writer: autobiographical works of Yasmina Khadra and their reception in France
Keywords: Algerian literature; Algerian history; Algerian civil war; uutobiography; autofiction